"Bad at Love": Halsey's Bisexual Display. Issue 4 (2nd October 2019) - Harman, Kate
Abstract: The 25-year old pop artist Halsey has recently made the jump from rising star to the top of the Billboard charts. What sets her apart from many other current muscians is not that she openly identifies as bisexual, or her willingness to play with gender performances, but rather is her hit song, "Bad at Love, " where the singer unequivocally details relationships with both men and women. Due to the uniqueness of the song - and its widespread commercial popularity - the accompanying music video is deemed significant, especially as it pertains to how she may create a bisexual display through various visual and verbal markers. Exactly how Halsey produces such a display in the video is examined here, concluding that the generation of her bisexual display is not distinctive to this video but rather a pattern of this artist, which is an area for further inquiry.